2017
DOI: 10.4049/jimmunol.1700643
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Blockade Promotes Epitope Spreading in Anticancer CD8+ T Cell Responses by Preventing Fratricidal Death of Subdominant Clones To Relieve Immunodomination

Abstract: The interactions between programmed death-1 (PD-1) and its ligands hamper tumor-specific CD8+ T cell (TCD8) responses, and PD-1-based ‘checkpoint inhibitors’ have shown promise in certain cancers, thus revitalizing interest in immunotherapy. PD-1-targeted therapies reverse TCD8 exhaustion/anergy. However, whether they alter the epitope breadth of TCD8 responses remains unclear. This is an important question because subdominant TCD8 are more likely than immunodominant clones to escape tolerance mechanisms and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 73 publications
1
33
1
Order By: Relevance
“…However, we had yet to determine if the focused TCR repertoire was associated with a loss in TCR recognizing subdominant Ags and subsequent recurrence of tumors, which we predict from our study. A recent mouse model study using viral SV40 large T Ag, however, showed that anti-PD therapy could promote epitope spreading by preventing fratricidal death of subdominant T cells (31). This finding is different from our results because we did not observe significant death of T cells recognizing dominant and subdominant Ags in our models.…”
Section: Discussioncontrasting
confidence: 99%
“…However, we had yet to determine if the focused TCR repertoire was associated with a loss in TCR recognizing subdominant Ags and subsequent recurrence of tumors, which we predict from our study. A recent mouse model study using viral SV40 large T Ag, however, showed that anti-PD therapy could promote epitope spreading by preventing fratricidal death of subdominant T cells (31). This finding is different from our results because we did not observe significant death of T cells recognizing dominant and subdominant Ags in our models.…”
Section: Discussioncontrasting
confidence: 99%
“…We found evidence for both viral (HSV-1 gB-specific) and melanoma (gp100-and TRP2-specific) CD8 + T cell responses, consistent with initial viral responses followed by cross presentation of tumor-associated antigens (34). Antigen spreading has previously been reported as a predictive biomarker of therapeutic responses for other forms of immunotherapy, including tumor vaccines and immune checkpoint inhibitors (35,36). We further observed that combination therapy promoted an IFN--regulated gene signature profile that has been associated with therapeutic responses to PD-1 blockade in patients with melanoma (18).…”
Section: Discussionsupporting
confidence: 74%
“…As a result, depending on their level of expression on the cell surface, CTLA-4 may interfere with CD80/CD86 binding. Several more inhibitors, such as lymphocyte activation gene 3, and V-domain Ig suppressor of T lymphocyte activation have been described, blocking these inhibitors by specific antibodies are being studied to increase the immune response in numerous cancers ( 42 , 43 ).…”
Section: T Lymphocyte Proliferationmentioning
confidence: 99%